الرد العلمي على شبهة ضياع أصل صحيح البخاري - المورعي، أحمد بن نافع (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2020)
تمثل السنة النبوية الأصل الثاني للتشريع الإسلامي، بعد القرآن الكريم، فهما منبعان للتشريع متعاضدان. وفي أيامنا هذه تعرضت السنة لحملات مغرضة من غلاة العلمانيين، والحداثيين، ومن أبرز الشبهات المثارة التي ينعقون ويشغبون حولها شبهة ضياع أصل صحيح البخاري، وأنه لا توجد نسخة خطية يعتمد عليها لصحيح البخاري إلى غير ذلك مما يرمون إلى الطعن في السنة وكتبها، فكان هذا البحث لدحض هذه الشبهة ورد هذا الافتراء، وقد أوردت نص هذه الشبهة وسردت من ذكرها قديما وحديثا، ورددت ردا علميا عليها، وقد تتبعت المنهج النقدي في عرض الشبهة وتفنيدها، وكان من أهم النتائج التي خرجت به هذه الدراسة: أن الروايات لصحيح البخاري موجودة متداولة، ومشتهرة، واختاروا رواية الفربرى بعد مقارنتها بغيرها، وتحديد نقاط الاختلاف بين النسخ.
The Prophetic Sunnah constitutes the second pillar of Islamic legislation after the Holy Qur'an. Both books are consolidated sources of legislation. These days, the Sunnah has been exposed to biased campaigns launched by extravagant secularists and modernists. One of those outstanding suspicions is that of losing the original book of Sahih Al-Bukhari and there is no manuscript written by such Imam.. Etc. Those suspicions meant to speak evil of the Sunnah and its books. Hence, this research intends to repudiate those suspicions and their allegations. The researcher has inserted the wording of those suspicions with reference to those who advocated them in ancient and modern times. The scientific response to those suspicions, as well as the whole research, follows the critical approach where the suspicions are both displayed and refuted. One of the most important findings of this research is that the narrations of Sahih Al-Bukhari are provided, common and well- known. They chose the narration of Al- Ferabery after comparison with other narrations, then they specified the points of difference in between the various versions.
Keywords: علم الحديث -- الأحاديث النبوية -- صحيح البخاري -- المعاجم العربية